The Application of Loose Parts Media in Play Activities to Improve Children's Letter Recognition - Sulvia Ninik Hidayati (SAHABAT: Jurnal Pendidikan Anak Usia Dini, 2026)
The main problem in this study is the still low ability of letter recognition in children, which is caused by the use of less interesting and rather conventional learning media. This study aims to determine the application of loose parts media in play activities to improve letter recognition in children at TK Dharma Wanita, Gayam Village, Gayam District, Bojonegoro Regency. This study uses a qualitative approach with a case study method. The research subjects consist of kindergarten group children and classroom teachers as the main informants. Data collection techniques are carried out through observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study show that the application of loose parts media in play activities can increase children's involvement in the learning process. Children appear more active, enthusiastic, and creative in arranging various objects into letter shapes. Playing activities using loose parts media also help children understand letter shapes more concretely through direct experiences. Social interaction among children also increases when they cooperate in arranging letters using the available materials.